Governance and Value-Added Tax Question in Nigeria: The Way Forward - Adeleke Adegbami; Oluwasesan Akanni Nofiu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
To perform its many responsibilities, the government needs to generate income from various and available sources. One of the sources is tax – value-added tax. Its acknowledged merits as an additional source of generating revenues for the government notwithstanding, VAT in Nigeria is fraught with difficulties. Given the foregoing, the study examined the associated issues with Nigeria's governance system and value-added tax administration. The study relies on the authors' observation of the events surrounding the VAT administration in Nigeria. Secondary data are sourced from the government's official documents, academic journals, textbooks, newspapers, magazines, and internet sources. The study showed that VAT, was introduced to get additional revenues to solve the problem of delivery of services, and the VAT transfer to the state government has a positive relationship with social development, while that of the local level does not. The study further revealed issues, of contentions surrounding VAT including - the constitutionality of the Federal Government to oversee the collection of VAT; and unfair disbursement of the proceeds from VAT to the component units of the federation. Furthermore, the study showed that the governance system of Nigeria has created an avenue whereby the VAT collection right, which normally should be an economic dispute, is tainted with politics and generates inter-ethnic issues. The study concluded that the value-added tax question is a pointer to the fact that Nigeria's fiscal federalism is problematic and, if not well-handled, can further polarize the country along different divides and impede its development.